Unlocking the Healing Potential: Exploring Risk and Safety in Manual Manipulation Including Tui Na Practices - Alfian, RM; Amalia, Anindini Winda; Handayani, Dwi Ratna Sari; Subu, Muhammad Arsyad; waluyo, imam (Medicor : Journal of Health Informatics and Health Policy, 2024)
Manual manipulative practices (MMPs), such as chiropractic spinal manipulation, osteopathic treatment, and Tui Na massage, are famous for improving musculoskeletal function but carry risks ranging from minor to severe side effects. Chiropractic therapy generally has minimal adverse effects, while Tui Na is less commonly used. A literature review on patient safety in MMPs involves evaluating studies, synthesizing findings, and identifying themes. While spinal manipulation can be beneficial, it may cause side effects like muscle soreness and headache and, in rare cases, severe complications like stroke. Reporting of adverse events has improved but still does not meet guidelines. Strategies to minimize risks include informed consent, thorough patient history, and adherence to clinical guidelines. These practices can enhance patient care and public health when applied with safety considerations.